2019
DOI: 10.3390/ijms20235877
|View full text |Cite
|
Sign up to set email alerts
|

CK2.3, a Mimetic Peptide of the BMP Type I Receptor, Increases Activity in Osteoblasts over BMP2

Abstract: Bone is one of the most important organs in the human body. It provides structure, function, and protection for other vital organs; therefore, bone maintenance and homeostasis are critical processes. As humans age, their bone mineral density decreases, which leads to diseases like osteoporosis. This disease affects one in two women and one in five men aged 50 and over. As the aging population increases, the interest and significance of studying this debilitating bone disease becomes more relevant. Current ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…Interestingly, several research groups have discovered a potential signaling disparity within the BMP pathway with those diagnosed with OP [13,14]. Further, we have previously reported that osteoblasts extracted from patients diagnosed with OP did not respond to BMP2 stimulation through mineralization assessments [15]. Mineralization deposits consist of mainly calcium and phosphate, thus indicating whether BMP2 is stimulating bone formation in OP patients when compared to control patients.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…Interestingly, several research groups have discovered a potential signaling disparity within the BMP pathway with those diagnosed with OP [13,14]. Further, we have previously reported that osteoblasts extracted from patients diagnosed with OP did not respond to BMP2 stimulation through mineralization assessments [15]. Mineralization deposits consist of mainly calcium and phosphate, thus indicating whether BMP2 is stimulating bone formation in OP patients when compared to control patients.…”
Section: Introductionmentioning
confidence: 94%
“…After the creation of a viable explant model, we wanted to further validate its effectiveness. Previously, we showed that primary osteoblasts isolated from OP patients led to decreased expression of the osteoblast specific markers, namely OC and ALP, when stimulated with BMP2 [15]. Here, we conducted the same study as described by Weidner et al, except we used the explant model and included control patients as a comparison.…”
Section: Bmp2 Stimulation Decreases Oc and Alp Expression In Op Patiementioning
confidence: 99%
See 3 more Smart Citations